Magnetic-Electric Dipole Antenna with Circular Polarization Feature and Directional Pattern with Improved Bandwidth - Seied Ali Banihashem; Pejman Mohammadi; Yashar Zehforoosh (مهندسی مخابرات جنوب)
This paper introduces a new and compact structure of a directional antenna consisting of an electric dipole and a truncated connection element. This antenna is fed by a Γ shaped power line. Wide impedance bandwidth in the frequency range of 1.3 GHz to 3 GHz will be observed in the output performance of this antenna. Base radiation patterns with high main loop and low side and back loop level are other features of the introduced antenna. The antenna design process is step-by-step and parametric based on the important parameters of antenna geometry. The main feature of the antenna is the realization of circular polarization at a high percentage of implicational bandwidth. The radiation patterns of orthogonal plates E & H along with left and right circular polarization patterns for the desired antenna have been extracted and analyzed. As predicted, there are many similarities between the E and H plane pattern, which indicates the accuracy of the design process. Is. The maximum total gain of the antenna in the designed frequency band is about 10 dBi..